Dolphins and porpoises - Patent, Dorothy Hinshaw (New York : Holiday House, 1987)
A general introduction to dolphins and porpoises, highlighting such areas as individual species, life cycles, anatomy, feeding habits, sonar system, and social organization.
"A Holiday House book."--Jacket.
Includes index.
Booklist.
School Library Journal.
Wilson's Junior High School.
5.7
Keywords: Dolphins -- Juvenile literature; Porpoises -- Juvenile literature; Dolphins; Porpoises; Dolphins; Porpoises